PENERAPAN STRATEGI MASTERY LEARNING UNTUK MENDESKRIPSIKAN HASIL BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN FISIKA FKIP UNRI PADA MATA KULIAH FISIKA MATEMATIKA I - Azizahwati Azizahwati (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2009)
This research aims to describe the results of mathematical physics major in faculty of PhysicsEducation of Riau University on the concept of Fourier series. Data collection instrument is a testof learning. Data were analyzed using descriptive analysis techniques that include the level ofstudent mastery of the material. Results of analysis of data showed a good level of mastery ofstudents categorized. Application of learning strategies can improve outcomes Masterymathematical physics student learning of physics education Prodi FKIP UNRI on Fourier seriesmaterial.